Approaches for Bull Fighting Event Tourism Brand Development of Songkla Province, Thailand - Wongphan, Chayanisa; Thitirattanakan, Saengsuree; Wichaikun, Apichat (Suan Dusit Graduate School Academic Journal, 2021)
This research aimed to 1) study the potential of brand development of bull fighting event tourism in Songkhla and 2) to propose the guidelines of brand development of bull fighting vent tourism in Songkhla. The qualitative research method and participatory action research were used. There were 32 key informants from governmental and private sectors, people, and tourists in Songkhla recruited by the purposive sampling method. The in-depth interview and participatory observation were used to collect the data. The findings revealed that 1) Songkhla had the potential to develop bull fighting event tourism in many aspects, including potential in providing information in order to present bull fighting event tourism to customers, having unique bull events, and being the center of bull fighting event tourism internationally and in ASEAN. 2) Guidelines for bull fighting event tourism brand development were (1) The building of networks and the affiliation of the international organizations for cooperation and coordination, which helped develop bull fighting event tourism, such as country, regional, and provincial confederations. (2) The determination of the places to hold bull fighting event tourism and the development of the key ideas about the places to hold these events. (3) The recommended extension of the longer period of the international event such as 5-10 days. (4) Songkhla’s strategic planning of bull fighting event tourism as to become the center of the event in ASEAN and internationally. (5) The creation of the website to support bull fighting event tourism brands in Songkhla province and the integration with social media such as facebook, twitter to develop the digital marketing on the internet.